Degtyaryova T. O. Fiction world of A. S. Grin in the literary discourse - Degtyaryova T. O. (Philological Treatises, 2020)
The article considers peculiarities of the A.S. Grin’s creative method and provides analysis for the impressionistic peculiarities of the writer’s fiction world.